2014
DOI: 10.1038/bjc.2014.491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of standard chemotherapy and antiangiogenic therapy on plasma markers and endothelial cells in colorectal cancer

Abstract: Introduction:The importance of the endothelium in angiogenesis and cancer is undisputed, and its integrity may be assessed by laboratory markers such as circulating endothelial cells (CECs), endothelial progenitor cells (EPCs), plasma von Willebrand factor (vWf), soluble E selectin, vascular endothelial growth factor (VEGF) and angiogenin. Antiantigenic therapy may be added to standard cytotoxic chemotherapy as a new treatment modality. We hypothesised that additional antiangiogenic therapy acts in a contrasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
1
5
1
Order By: Relevance
“…Surprisingly, subjects with a pre-treatment sE-selectin concentration lower than 25.04 ng/mL appear to have a higher risk of disease recurrence. However, this observation is inconsistent with previous studies of Ramcharan et al, Mann et al and Muz et al [ 36 , 37 , 38 ]. Since, we should expect opposite results due to the fact that high sE-selectin concentration is associated with a shorter survival rate [ 50 ].…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Surprisingly, subjects with a pre-treatment sE-selectin concentration lower than 25.04 ng/mL appear to have a higher risk of disease recurrence. However, this observation is inconsistent with previous studies of Ramcharan et al, Mann et al and Muz et al [ 36 , 37 , 38 ]. Since, we should expect opposite results due to the fact that high sE-selectin concentration is associated with a shorter survival rate [ 50 ].…”
Section: Discussioncontrasting
confidence: 92%
“…Authors suggest to analyze their results with caution due to limited number of patients in each subgroups. They speculate that it was probably nonspecific response of the endothelium to the different types of treatment [ 36 ]. Considering that sE-selectin is involved in leukocyte and cancer cell extravasation, homing, adhesion, proliferation, cellular dormancy, drug resistance, and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CEP may generate new blood vessels in the tumor (vasculogenesis) whereas CEC could derive from shedded endothelial cells [ 13 ]. The change of CEC and CEP levels we observed in this study was comparable to other studies [ 13 , 36 , 37 ]. Moreover we found that other CEC subpopulations such as VEGFR2 + CEC, whose pathophysiological role has not been investigated intensively so far, react differently to antiangiogenic therapies and decrease at the time point of resistance.…”
Section: Discussionsupporting
confidence: 92%
“…Several comorbid conditions affect patients with cancer, which influence their treatment in the setting of PCI. While cancer and its treatment can predispose patients to bleeding tendencies and thrombocytopenia, neoplasia by itself is a pro-coagulant state ( 14 ). This poses a unique challenge and highlights the need to evaluate thrombosis and bleeding risks carefully.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a unique challenge and highlights the need to evaluate thrombosis and bleeding risks carefully. In the setting of PCI, this information has a tremendous impact on the options for stenting and antiplatelet therapy ( 14 ). Several clinical studies have proven the superiority of DES over BMS in reducing the risk of restenosis and stent thrombosis compared with bare-metal stents (BMS) in non-cancer high-risk patients ( 9 ).…”
Section: Discussionmentioning
confidence: 99%